Reconstruction of the Islamic Education Paradigm from Classic to Modern Mazhab - Bastami, Bastami; Maulana, Ilham (Maharot : Journal of Islamic Education, 2024)
The reconstruction of the paradigm of Islamic religious education is an effort to adjust Islamic religious education to the increasingly modern demands of the times, global educational challenges, and the development of science and technology. This exploratory effort involves changes in methodology, curriculum, and the objectives of Islamic religious education from the classical school to the modern school. The goal of this reconstruction is to transform and develop the classical school, which initially emphasized memorization and textual understanding, into a modern Islamic religious education with an inclusive, contextual approach, oriented towards the development of practical skills and a deep understanding of Islamic values. The research method used is a qualitative approach with a type of library research. Data analysis is carried out using content analysis methods, including data reduction, grouping data into specific units, data classification, and data interpretation. The results of the reconstruction of classical Islamic religious education, which used traditional methods such as memorization and textual understanding, are then developed into a modern school by integrating Islamic values with science and technology in a contextual manner. The adaptation of Islamic religious education is necessary to create a space for the integration of Islamic values with the dynamics of modern times.